2020
DOI: 10.2478/hukin-2019-0143
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Incremental Running Field and Treadmill Tests in Young Soccer Players

Abstract: The purpose of this study was to compare the incremental running tests performed by young soccer players on a treadmill (Tr) and in the field (FTcod: 100 m change of direction and FTcir: 100 m circle). Nineteen players (average age 17.4 ± 1.1 years; body height 172.0 ± 5.7 cm; body mass 68.9 ± 6.7 kg) volunteered to perform incremental Tr , FTcod and FTcir running tests. In all three tests, players ran for 3 min at 8, 10, 12 and 14 km∙h-1 and were given a 1 min rest interval between subsequent stages. Blood la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…A higher muscular mass recruitment or even recruitment of more type II muscle fibers 35 , 36 may be responsible for increases in blood lactate concentration at a given intensity. The type of fiber recruitment may explain the higher values for this variable when using the NMT than on the MT, as found in our study, and for overground running, as found elsewhere 37 39 . This way, running on an NMT could offer higher stress for the glycolytic pathway of ATP resynthesis, even with similar relative intensities than on the MT.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A higher muscular mass recruitment or even recruitment of more type II muscle fibers 35 , 36 may be responsible for increases in blood lactate concentration at a given intensity. The type of fiber recruitment may explain the higher values for this variable when using the NMT than on the MT, as found in our study, and for overground running, as found elsewhere 37 39 . This way, running on an NMT could offer higher stress for the glycolytic pathway of ATP resynthesis, even with similar relative intensities than on the MT.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, studies comparing blood lactate concentration at iLT obtained by an incremental test performed on different surfaces have often found lower values on the MT than the on-field testing 37 39 . Furthermore, although the results presented here could not compare running on an NMT with overground, one previous investigation on 5-km performance registered higher post-exercise blood lactate concentration on the NMT than overground, without differences in O 2 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The subjects examined were eighteen young male football players (17.4±0.8 years). And more latterly, Köklü et al (2020) also analyzed the HR responses of male football players (n = 19; 17.6±1.1 years) by means of a two-part incremental running test, with speeds of 8, 10, 12, and 14 km•h −1 in the first part, and from 15 km•h −1 and with increments of 1 km•h −1 until volitional exhaustion in the second part. Three experimental conditions were compared: motorized treadmill running under laboratory conditions, field running with 180-degree change of direction every 100 meters, and field running on a circular 100 m track.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mathematical equations have been generated to calculate the target heart rate as a function of the desired percentage of exercise intensity, and physical activity intensity levels have also been defined based on the heart rate reserve and the maximal heart rate (American College of Sports Medicine, 2014; Kenney et al, 2019). @ @ @ @ Diverse studies have reported results of the comparison between the HR responses attained during running overground and on level-grade treadmill (Brookes et al, 1971;Ceci & Hassmén, 1991;Chu et al, 2010;Di Michele et al, 2009;Jones & Doust, 1996;Köklü et al, 2020;Kunduracioglu et al, 2007;Maksud et al, 1971;McMurray et al, 1988;Miller et al, 2019;White et al, 1998;Yngve et al, 2003). Athletes and non-athletes have been evaluated, and constant and progressive incremental protocols have been proposed.…”
Section: Introductionmentioning
confidence: 99%